An Exploratory Study of the Factors of Inclusion in a Multinational Organization - El-Segaier,Zakaria (2019)
Purpose: The purpose of this study is to explore and identify the factors leading to or inhibiting inclusion, and how these do so. Methodology: I conduct a qualitative case study using semi-structured interviews of respondents within an anonymous case company named Company X, and use pattern matching to both test factors of inclusion found in the diversity and inclusion literature, but also identify new factors that are unmentioned in the literature. Theoretical perspectives: The study is based on Shore, Randel, Chung, Dean, Ehrhart & Singh’s (2011: 1265) definition of inclusion as “the degree to which an employee perceives that he or she is an esteemed member of the work group through experiencing treatment that satisfies his or her need for belongingness and uniqueness”. The study also builds on other theory in the diversity and inclusion literature to identify already explored factors and test them. Empirical foundation: Data was collected through semi-structured interviews with four employees, four managers, and one vice-president at Company X using pre-prepared interview guides. Data was also collected from internal and external communication. Conclusions: My study first tests factors of inclusion from the diversity and inclusion literature, and finds that some factors have a strong impact on the inclusion of employees [access to rewards and promotions, participation in decision-making, and leader-member exchange], whereas others have a weak impact [access to information, job complexity & group autonomy & creativity, and support from supervisors & co-workers]. I also find factors of inclusion not mentioned in the diversity and inclusion literature [commitment variation, competitor’s D&I, local demographic diversity, tenure, employee turnover, level of English language, internal communication, transparency, product life-cycle, number of minorities, proactive inclusion, physical proximity to manager, and experience] and that these have a strong impact on the inclusion experience of employees. Implications and possibilities for further research are discussed.